1994
DOI: 10.1002/1097-0142(19940115)73:2<445::aid-cncr2820730233>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, multicenter study comparing the efficacy and tolerability of tropisetron, a new 5-HT3 receptor antagonist, with a metoclopramide-containing antiemetic cocktail in the prevention of cisplatin-induced emesis

Abstract: Background. Chemotherapy‐induced emesis is one of the most disturbing side effects in cancer therapy. Thus, antiemetic treatment is a mandatory adjunct in emetogenic chemotherapy. Methods. Tropisetron (Navoban, Sandoz Pharma Ltd., Basel, Switzerland), a new 5‐HT3 receptor antagonist, was compared in a randomized multicenter trial with a high‐dose metoclopramide‐dexamethasone cocktail for the prevention of nausea and emesis during cisplatin‐containing chemotherapy. Two hundred fifty‐nine chemotherapy‐naive pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

1995
1995
2003
2003

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 23 publications
1
12
0
1
Order By: Relevance
“…The complete plus major control rates were 77%, 81%, 86%, 67% and 75% for cycles l to 5, respectively, which falls within the range of 53 -76% previously reported by other investigators (2 -6). In our study, the outcome for control of delayed nausea and vomiting was good, the complete plus major control rates were 82%, 69%, 72%, 73%, and 80% for cycles 1 -5, respectively, which was an improvement on the other reports (7,8). This may reflect the better control of acute nausea and vomiting plus the effect of oral tropisetron given on days 2-6.…”
Section: Discussionsupporting
confidence: 52%
“…The complete plus major control rates were 77%, 81%, 86%, 67% and 75% for cycles l to 5, respectively, which falls within the range of 53 -76% previously reported by other investigators (2 -6). In our study, the outcome for control of delayed nausea and vomiting was good, the complete plus major control rates were 82%, 69%, 72%, 73%, and 80% for cycles 1 -5, respectively, which was an improvement on the other reports (7,8). This may reflect the better control of acute nausea and vomiting plus the effect of oral tropisetron given on days 2-6.…”
Section: Discussionsupporting
confidence: 52%
“…Finally two open, randomized, multicenter studies have been published [28,29]. The first compared tropisetron (5 mg i.v.…”
Section: Introductionmentioning
confidence: 99%
“…There has been marked progress in the control of chemotherapy-induced emesis over the past few years. Clinical trials have confirmed the value of serotonin receptor antagonists in the prevention and treatment of acute drug-induced nausea and vomiting [3,[8][9][10]14]. In recent years there has been a market trend to increasing dose intensity in cancer chemotherapy, with or without peripheral blood stem-cell support.…”
Section: Introductionmentioning
confidence: 99%